2016
DOI: 10.3847/0004-637x/822/2/64
|View full text |Cite
|
Sign up to set email alerts
|

SDSS J163459.82+204936.0: A Ringed Infrared-Luminous Quasar With Outflows in Both Absorption and Emission Lines

Abstract: SDSS J163459.82+204936.0 is a local (z = 0.1293) infrared-luminous quasar with L IR = 10 11.91 L ⊙ . We present a detailed multiwavelength study of both the host galaxy and the nucleus. The host galaxy, appearing as an early-type galaxy in the optical images and spectra, demonstrates violent, obscured star formation activities with SFR ≈ 140M ⊙ yr −1 , estimated from either the polycyclic aromatic hydrocarbon emission or IR luminosity. The optical to NIR spectra exhibit a blueshifted narrow cuspy component in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 105 publications
(124 reference statements)
1
33
1
Order By: Relevance
“…Two principal components are superposed into the model: (1) the quasar composite and (2) the host galaxy starlight. The quasar composite (also used in Liu et al 2016) is created by splicing the UV to optical quasar composite of Vanden Berk et al (2001), the NIR quasar composite of Glikman et al (2006), and the FIR quasar composite of Netzer et al (2007). It contains the nucleus power-law continuum, the broad/narrow emission lines from the broad/narrow line regions, the NIR and MIR emission from the torus, and the more or less starlight contamination.…”
Section: Broadband Spectral Energy Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two principal components are superposed into the model: (1) the quasar composite and (2) the host galaxy starlight. The quasar composite (also used in Liu et al 2016) is created by splicing the UV to optical quasar composite of Vanden Berk et al (2001), the NIR quasar composite of Glikman et al (2006), and the FIR quasar composite of Netzer et al (2007). It contains the nucleus power-law continuum, the broad/narrow emission lines from the broad/narrow line regions, the NIR and MIR emission from the torus, and the more or less starlight contamination.…”
Section: Broadband Spectral Energy Distributionmentioning
confidence: 99%
“…We picked them up again during the series study of the reddening AGNs (e.g., Li et al 2015;Liu et al 2016;Pan et al 2017;Zhang et al 2017). We study the He I* λ10830 absorption lines (the first detection reported by Leighly et al 2011) as well as the continuum, and hydrogen Balmer/Paschen broad emission lines of these objects.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction is generally 10%-20% in optical-selected quasars (e.g., Trump et al 2006;Gibson et al 2010;Zhang et al 2014) and~30% (e.g., Maddox et al 2008) or even 44% (Dai et al 2008) in NIR-selected quasars. We consider that BAL and BEL outflows may be different appearances viewed from different inclination angles but representing the same physical component, which is suggested by many works (e.g., Richards et al 2011;Wang et al 2011;Liu et al 2016); the global covering fraction of BEL outflows will follow these values. The value we obtained in SDSS J0006+1215 is slightly smaller than those estimated from optical-selected BAL quasars.…”
Section: Kinetic Luminosity and Mass Flux Of The Outflowsmentioning
confidence: 99%
“…This is because the BALs have high-speed blueshifted (up to a velocity ofṽ c 0.2 ) and broad-width (at least 2000 km s −1 ) troughs from a wide range of species, such as Mg II, Al III, Fe II, N V, C IV, Si IV, and O VI (e.g., Weymann et al 1991;Hall et al 2002;Reichard et al 2003; Trump et al 2006; Gibson et al 2010;Zhang et al 2010), and even from the hydrogen Balmer series (e.g., Hall 2007;Ji et al 2012Ji et al , 2013Zhang et al 2015b) and metastable He I (e.g., Liu et al 2015Liu et al , 2016, whose obvious features allow the BALs to be easily detected and measured. Unfortunately, the broad and narrow blueshifted-ELs (BBELs and BNELs) are generally mixed with the normal broad or narrow lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation